2017
DOI: 10.1055/s-0043-110050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the bleeding risk with various antithrombotic therapies after gastric endoscopic submucosal dissection

Abstract: Background and study aims  Patients receiving antithrombotic drugs have a higher risk of postoperative bleeding and thromboembolic events related to endoscopic procedures. The aim of this study was to evaluate the relationship between various antithrombotic therapies and bleeding after gastric endoscopic submucosal dissection (ESD) (post-ESD bleeding). Patients and methods  Among 529 consecutive gastric ESD procedures (483 patients with 579 legions), 100 patients with 121 lesions who underwent 108 procedures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 35 publications
3
31
1
Order By: Relevance
“…Recently published supplementary issue of JGES guidelines for management of patients taking anticoagulants suggests the possibility of continuation of warfarin instead of heparin bridging therapy during high‐bleeding‐risk endoscopic procedures because many studies showed a high incidence of delayed bleeding after gastric ESD in patients received heparin bridging therapy (10.8–61.5%; Table ) …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published supplementary issue of JGES guidelines for management of patients taking anticoagulants suggests the possibility of continuation of warfarin instead of heparin bridging therapy during high‐bleeding‐risk endoscopic procedures because many studies showed a high incidence of delayed bleeding after gastric ESD in patients received heparin bridging therapy (10.8–61.5%; Table ) …”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
“…77,78 In terms of multiple antithrombotic therapies, the JGES guidelines recommend that thienopyridine should be withdrawn or replaced by aspirin or cilostazol monotherapy for high-risk bleeding procedure. 70 Because of the high delayed bleeding rates after gastric ESD in patients taking multiple antithrombotics including anticoagulants, ranging from 11.1% to 45.4% (Table 5), 75,76,[79][80][81][82][83][84][85] use of multiple antithrombotic drugs is one of the high risk factors. A meta-analysis indicated that the risk of delayed bleeding after gastric ESD in regular users of multiple antithrombotic drugs was significantly higher than never users (odds ratio 5.17 [95% CI: 3.13-8.54]).…”
Section: Adverse Events Related To Gastric Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2012 guidelines for gastroenterological endoscopy in patients undergoing antithrombotic treatment in Japan recommended replacing warfarin with heparin for those at a high risk of bleeding . However, subsequent studies indicated that patients on heparin replacement therapy had a higher incidence of delayed hemorrhage than those continuing warfarin . When analyzing the risks of hemorrhage during heparin replacement therapy, Dong et al performed a meta‐analysis that included 10 540 patients from 16 studies, showing that heparin replacement therapy could increase the incidence of post‐ESD bleeding.…”
Section: Risks Of Bleeding After Gastric Esdmentioning
confidence: 99%
“…If their INR levels remain elevated, a small amount of vitamin K should be given a day before the operation while paying attention to the possibility of an embolism. If the patient is at a high risk of thrombosis, warfarin should be sustained when INR is within the scope of treatment, or can be temporarily replaced with DOAC . The Japanese guidelines 2017 also recommend patients to stop taking DOAC if they are at a low risk of thrombosis; while those at a high risk of thrombosis should continue to take DOAC until the day before operation and interupt DOAC on the morning of the operation.…”
Section: Precautions Against Bleeding After Gastric Esdmentioning
confidence: 99%